Overheating and passive habitability: indoor health and heat indices. Issue 1 (2nd January 2016) - Holmes, Seth H.; Phillips, Thomas; Wilson, Alex
Abstract : As extreme heat and weather events are predicted to increase due to global warming, the risk of human heat stress within buildings will increase. To be resilient, buildings will need the capacity to provide habitable indoor conditions without power for limited amounts of time. Additional indoor thermal standards are required for public health to address 'passive habitability' during power outages. Current research on building-related heat stress and numerous heat indices is examined in relation to the development of a new heat-safety metric for use in passively conditioned buildings. Most indoor overheating research relies on outdoor temperature data and has no common indoor heat index for evaluating indoor heat stress. A recommendation is made for using the wet-bulb globe temperature (WBGT) and predicted heat strain (PHS) indices for modelling and monitoring of indoor heat stress in healthy adult populations because both indices utilize the primary thermoregulation variables, have associated heat-stress thresholds, and can be assessed or tracked with existing environmental monitoring methods and predictive energy modelling techniques. Further research is recommended on health effects and exposure limits of vulnerable populations, and the variation in thermal factors within buildings and the building stock.